Health Education Affected the Anxiety Levels of Pregnant Women In Facing Childbirth - Evita Widyawati; Friska Oktaviana; Sundari (STIKes Patria Husada Blitar, 2025)
Indonesian women within the 20-to-44-year age bracket are particularly vulnerable to experiencing depression or anxiety in the context of vaginal childbirth, with a reported risk of 10% to 25%. Of this cohort, a notable proportion, specifically 10% to 15%, may experience these psychological difficulties as complications during the delivery process, and the risk of anxiety in caesarean section patients is 15-25%. This was pre-experimental research with a One-Group Pretest and Posttest design. The sample was 40 respondents taken by a Non-Random Sampling technique; Accidental Sampling. This research was conducted October 15 - November 10 2023. The instrument used a questionnaire sheet. A Wilcoxon test was employed for data analysis, demonstrating a significant decrease in anxiety levels after an educational intervention. The mean anxiety score decreased from 2.74 before education to 1.83 afterward, yielding a p-value of 0.001 (which is less than the significance level of 0.05). These results underscore the importance of healthcare providers delivering more comprehensive education on anxiety management to pregnant women facing childbirth, with the aim of alleviating pre-delivery fear and apprehension.